A Spatial Analysis of Dengue Hemorrhagic Fever (DHF), Hygiene, and Latrines in Depok City in 2020 - Salsabila Naim; Sutanto Priyo Hastono; Sukma Rahayu; Martina Puspa Wangi (Universitas Airlangga, 2022)
Introduction: Depok is one of the areas in West Java with an increasing Dengue Hemorrhagic Fever (DHF) trend. In 2017, 548 DHF cases were reported, and this increased to 1,276 cases in 2020. It is necessary to control and map influencing factors on DHF incidence to detect endemic areas and reduce its spread. Methods: This study was conducted to identify a spatial autocorrelation between DHF, hygiene, and clean latrines in Depok in 2020. The data were obtained from the Depok City's Health Profile published in 2020. The Moran's I and local indicator of spatial association (LISA) univariate and bivariate analysis methods were performed using the GeoDa application. Results and Discussion: DHF (Moran's I = 0.32), hygiene (Moran's I = 0.25) and clean latrines (Moran's I = 0.24) had a significant positive autocorrelation with the clustered pattern. This indicated that data patterns clustered had similar characteristics in the area. Villages in the high-high DHF incidence quadrant were Kukusan, East Beji, Beji, Tanah Baru, Kemirimuka, Depok, Pancoran Mas, and Depok Jaya. In general, there was no spatial autocorrelation neither between DHF and hygiene, nor DHF and clean latrines. However, in some urban villages, significant autocorrelations between these variables were discovered. Conclusion: DHF incidence in this study formed a clustered pattern. Influencing factors, such as hygiene and clean latrines, followed the same pattern. Besides that, a spatial autocorrelation was also apparent between DHF and hygiene, as well as DHF and clean latrines in several urban villages in Depok.